Islamic Legal Philosophy in the Context of Normative Pluralism among Southeast Asian Muslims - Indriya Fathni; Johni Najwan; Sulalatun Nikma; Mujiburrohman Mujiburrohman; Leila Hassan (Insani: Jurnal Pranata Sosial Hukum Islam, 2026)
Islamic law can no longer be understood as a single, definitive and hegemonic normative authority, but rather as a dynamic, dialogical epistemic horizon continually negotiated through the interaction among sharīʿah, customary law and state law. This study aims to provide a comprehensive analysis of the philosophy of Islamic law within the context of Muslim normative pluralism in Southeast Asia, focusing in particular on how the philosophical principles of Islamic law are employed to understand, explain and evaluate the diversity of norms emerging within multicultural societies. This study employs a qualitative, interpretative-critical approach to Islamic legal philosophy, with conceptual and contextual analysis. The findings indicate that the dynamics of the relationship between Islamic law, customary law and state law in Indonesia, Malaysia and Brunei Darussalam constitute a significant source for the revitalisation of the epistemology of Islamic law itself, as law is no longer positioned as a monolithic, closed system, but rather as an arena for ethical dialogue that is continually shaped through social practice, normative negotiation and collective ijtihād. Through the integration of the concepts of epistemological hybridisation, normative co-existence and negotiation, and the development of maqāṣid al-sharīʿah grounded in pluralism, this study broadens the horizons of Islamic legal philosophy from the classical normative framework towards a transformative paradigm that is more inclusive, adaptive and responsive to the complexities of multicultural societies, whilst affirming that the flexibility of Islamic law is not a deviation from sharīʿah, but rather a fundamental prerequisite for its sustainability and relevance in the face of contemporary social dynamics.